ON CONVOLUTION TRANSFORMS WHOSE INVERSION FUNCTIONS HAVE COMPLEX ROOTS - Hakobian, S. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
For convolution transforms it has been received inversion formula, when $φ(x) \in L^{2}(-∞, +∞)$, and inversion functions $E(x)=\prod\limits^{∞}_{k=1}\Big(1- \dfrac{s^2}{a_k^2}\Big)$ have complex roots satisfying to conditions $\sum\limits_{k=1}^{∞}